Lyophilization Serves as an Effective Strategy for Drug Development of the α9α10 Nicotinic Acetylcholine Receptor Antagonist α-Conotoxin GeXIVA[1,2] - Zhiguo Li; Xiaolu Han; Xiaoxuan Hong; Xianfu Li; Jing Gao; Hui Zhang; Aiping Zheng (Marine Drugs, 2021)
α-Conotoxin GeXIVA[1,2] is a highly potent and selective antagonist of the α9α10 nicotinic acetylcholine receptor (nAChR) subtype. It has the advantages of strong efficacy, no tolerance, and no effect on motor function, which has been expected help patients with neuropathic pain. However, drug development for clinical use is severely limited owing to its instability. Lyophilization is applied as the most preferred method to solve this problem. The prepared lyophilized powder is characterized by differential scanning calorimetry (DSC), powder X-ray diffractometry (PXRD), and Fourier transform infrared spectroscopy (FTIR). Molecular simulation is also used to explore the internal distribution and forces formed in the system. The analgesic effect on paclitaxel-induced neuropathic pain following single and 14-day repeated administrations are evaluated by the von Frey test and the tail-flick test. Trehalose combined with mannitol in a ratio of 1:1 is employed as the excipients in the determined formulation, where trehalose acts as the stabilizer and mannitol acts as the bulking agent, according to the results of DSC, PXRD, and FTIR. Both GeXIVA[1,2] (API) and GeXIVA[1,2] lyophilized powder (formulation) could produce stable analgesic effect. These results indicated that GeXIVA[1,2] lyophilized powder could improve the stability and provide an effective strategy to push it into clinical use as a new analgesic drug.